Implementasi Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru - Sari, Danar Yunita Ria; Abdullah, Ghurfon; Ginting, Rosalina Br. (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The performance of SDN Padasugih 01 teachers is in the good category and is able to make the school superior, its students excel at class, sub-district and district levels. The good performance of Padasugih 01 State Elementary School teachers cannot be separated from the role of the principal as a supervisor who always provides encouragement and input to the teachers. The principal of Padasugih 01 State Elementary School is very consistent in improving teacher performance in the school he leads. The focus of the problem in this research is the Implementation of the Principal's Academic Supervision in improving teacher performance at Padasugih 01 Elementary School, Brebes Regency with the following research sub-focuses: 1) Principal academic supervision planning schools in improving the performance of teachers at SD Negeri Padasugih 01. 2) Implementation of the principal's academic supervision in improving teacher performance at SD Negeri Padasugih 01. 3) Evaluation and follow-up of the principal's academic supervision in improving teacher performance at SD Negeri Padasugih 01. Objectives of This research is to analyze how academic supervision carried out by the school principal can contribute to improving teacher performance at SDN Padasugih 01. The practical benefits are for teachers, schools and education services to be taken into consideration in improving teacher performance even better. This research uses a qualitative approach, with data collection techniques in the form of observation, interviews and documentation.  The research results show that the implementation of academic supervision at SDN Padasugih 01 is carried out through several stages, namely planning, implementation, evaluation and follow-up. At the planning stage, the principal prepares a supervision program that involves all teachers. At the implementation stage, supervision is carried out periodically with a focus on class observations, providing constructive feedback, and reflective discussions. Evaluation is carried out to assess the effectiveness of supervision and teacher performance. Follow-up takes the form of training and professional development through training and workshops. The implementation of academic supervision has proven to be effective in improving teacher performance at SDN Padasugih 01. Teachers feel more motivated and focused in developing their teaching abilities, as seen from the improvement in learning quality and student learning outcomes. Based on the conclusions above, it is recommended that academic supervision continue to be improved and implemented with a sustainable professional development program to improve teacher performance at SDN Padasugih 01.